STUDYING THE EFFECT OF COLLABORATIVE DIALOGUE TECHNIQUE ON GRADE TEN STUDENTS’ VOCABULARY ACQUISITION - Nurul Hasanah Fajaria; Sumayyah Asy Syarifah (Lingua, 2017)
This study examines the effect of using collaborative dialogue technique on EFL learner’s vocabulary acquisition at SMA Tunas Markatin Rawamangun. The purpose of this research is to find out whether or not there is the effect of using collaborative dialogue technique on students’ vocabulary acquisition. The subject consisted 50 students and divided into two classes (experimental class and control class), consist of 25 students in each class. The sampling technique was randomize sampling. To collect data the researcher used two instruments in the form of objective multiple choice each numbering 30 for both experiment class and control class out of 60 question items for experiment class and control class having been tried out at class X at SMA Vinama, Bekasi. The score obtained from the try out class were used to analyze the validity, reliability, discrimination power and difficulty index of each question item in the two instruments. The analysis using SPSS-based One-Way Anova formula produced significance (Sig) value of 0.000. Since the significant value was smaller than (<) Alpha 0, 05, Ho is rejected and Ha is accepted. Accordingly the research concluded that there was significant effect of collaborative dialogue on grade ten students’ vocabulary acquisition at SMA Tunas Markatin, Rawamangun in the academic Year of 2016/2017.